ANALISIS PROBLEMATIKA DAN ALTERNATIF PEMECAHAN MASALAH PEMBELAJARAN MATEMATIKA DI SMP - I komang Sukendra; Sumandya I Wayan (Emasains : Jurnal Edukasi Matematika dan Sains, 2020)
This study aims to determine alternative problem solving in the 2013 curriculum book and human resources in mathematics learning in junior high schools. This research is a qualitative research, using a case study design method. Mathematics subjects need to be given to all students starting from elementary school, to equip students with the ability to think logically, analytically, systematically, critically, innovatively and creatively, as well as the ability to work together. Mathematical skills or skills are part of the life skills that students must have, especially in developing reasoning, communication, and solving problems faced in students' daily lives. Mathematics is always used in all aspects of life, all fields of study require appropriate mathematical skills, is a strong, concise and clear means of communication, can be used to present information in various ways, improves logical thinking skills, accuracy and spatial awareness, gives satisfaction to business solve challenging problems, develop creativity, and as a means of raising awareness of cultural developments. The above can be realized if adequate facilities and infrastructure and the availability of qualified human resources mathematics teachers.